Improving Paud Information Services to the Community Through the Socialization of Paud Information Systems (SIMPAT) at the City of Tidore Education Department - *Gamaria Mandar; Abdul Haris Muhammad; Fitria Auliah; Daniel Siloam (Universitas Syiah Kuala, 2022)
Information is one of the important components in coordinating both near and far distances. The Tidore City Education Office is no exception, especially in the field of Early Childhood Education (PAUD). Dissemination of information by only relying on messages directly to the school and the community. This was evaluated as not very effective considering the area of the city of Tidore which consists of several small islands. Besides that, people who want to get information about early childhood education schools in the city of Tidore are still having difficulties because there is no accessible information media. This service is carried out to build the Early Childhood Information System (SIMPAT) to facilitate various parties, both in the early childhood education department, in providing information and the public in obtaining complete and detailed information on early childhood schools in the city of Tidore Islands. The method of training and mentoring in the socialization carried out shows that the early childhood information system (SIMPAT) is more efficient, saves time and the information needed by the community becomes much easier to convey